Does pain affect executive function in sickle cell disease?. (24th May 2012) - Seymour, EL; Hollocks, M; Roberts-Harewood, M; Robins, A; Wilkey, O; Morgan, MA; Kirkham, FJ
Abstract : Aims: Research in populations with sickle cell anaemia (SCA) has consistently found differences from healthy controls on tests of executive function (EF), attributed to the elevated stroke risk. In older adults without SCA there is an association between pain and mental flexibility. The aims of this study were to investigate the executive function performance of a group of SCA children across a single test battery and the possibility that chronic pain impacts upon these skills. Methods: Patients with SCA were recruited via their consultants at outpatients clinics. Sibling controls and other ethnically matched children were recruited via the community. The Weschler Abbreviated Scales of Intelligence (WASI): two-sub-test version was administered together with five of the nine available sub-tests of the Delis Kaplan Executive Function System (D-KEFS), representing a range of different skills: the trail-making, the design fluency, colour-word interference, sorting and tower tests. Composite scores were created for each of the DKEFS sub-tests. Current pain was measured using the Faces Pain Scale-Revised (FPS-R). Frequency of pain was measured via self-report of the number of pain episodes over the past year. A number of t-tests, followed by correlations, were then employed to compare performance across the two groups. Results: Eight controls (3 male), mean age 11 y 3 m (9 y 8 m-14 y 8 m) and 14 (11 male) children with SCA, mean age 13 y 4 m (10 y 7 m-17 y 6 m) were recruited. There was a significant difference between the frequency of pain episodes in the SCA and control groups, t (20)=−2.56, p=0.019. T-tests showed no significant differences at the 95% confidence interval in FPS-R scores, any of the DKEFS sub-tests, or FSIQ. No significant correlations were found between either frequency of pain episodes or current pain, and any of the composite EF sub-test scores. Discussion: We found no evidence of impaired performance by the SCA group on any of the EF sub-tests. The SCA group reported significantly more frequent pain episodes, and a wider range of pain levels on the day of testing but there was no association between current pain, or pain frequency, and EF test performance, perhaps explained by the subjective nature of pain, and differences in pain perception.